Coal and peat fires : a global perspective. - Stracher, Glenn B.; Sokol, Ellina V.; Prakash, Anupma (Elsevier Science, 2015)
Coal and Peat Fires: A Global Perspective, Volumes 1-4, presents a fascinating collection of research about prehistoric and historic coal and peat fires. Magnificent illustrations of fires and research findings from countries around the world are featured-a totally new contribution to science. This third of four volumes in the collection, Coal Fires - Case Studies, examines in detail specific coal fires chronicled in a number of locations around the world including Brazil, the Czech Republic, Germany, Malawi, Poland, Russia, Spain, Tajikistan, the United States, Venezuela, and others. Auth.